"Hot-for-Teacher": Statutory Rape or Postfeminism in Pretty Little Liars?. Issue 1 (1st March 2020) - Crookston, Shara
Abstract: In this article I explore the highly problematic but wildly acclaimed romantic relationship between Aria Montgomery, a high school junior, and her English teacher Ezra Fitz in the television series Pretty Little Liars . This partnership normalizes gendered power imbalances often common to heterosexual partnerships, yet fervent fans have supported the duo enthusiastically, dubbing the couple #Ezria in blogs and social media. As we know, much research shows that along with unintended pregnancy, young girls who are victims of child sexual abuse by adult males suffer from depression. These outcomes are not shown in Pretty Little Liars : the series ends with Aria marrying her teacher in an example of a happily-ever-after ending, thereby reinforcing postfeminist ideas that Aria's self-efficacy has never been compromised. I argue that in the era of #Metoo, the exploration of power in heterosexual romantic relationships on television shows aimed at adolescent girl audiences is a site for critical analysis.